Differentiated Teaching and Learning Applied in English Classes of Phase F of Senior High School - Azhari, Zakiyurrahman; Zainil, Yetti (Universitas Negeri Padang, 2024)
This study aims to describe how teachers applied differentiated teaching and learning in English classes of phase F Senior High Schools based on the Merdeka curriculum and figure out the problems they commonly encountered in this type of instruction. The data was gathered by interviewing and observing English teachers who taught phase F grade XI of SMA Negeri 7 and SMA Negeri 10 Padang in the first semester of the 2023-2024 academic year representing English teachers of batch I and II Sekolah Penggerak in Padang who were selected by applying purposive sampling. First interview was conducted to investigate how teachers identified student’s learning needs and observation was conducted to investigate how teachers applied differentiated teaching and learning in the classes. Another interview was conducted to find out and describe the problems commonly encountered in this type of instruction. The results show that both teachers A and B identified students' learning needs (readiness) by applying initial formative assessments and taking the data provided by counselling teachers about students' interests and learning profiles. Both teachers adjusted their instruction with relatively similar content differentiation strategies due to the level of student readiness and language barriers. Each teacher applied various processes of differentiations in the types of activity, tasks, media and the level of assistance provided. However, teacher B showed more engagement in personal assistance, scaffolding and tiered tasks. Teacher A offered less consistent product alternatives while teacher B was more consistent and challenged student’s creativity in working by utilizing technology. Accordingly, teacher A faced more obstacles than teacher B.